Tumor cell-based liquid biopsy using high-throughput microfluidic enrichment of entire leukapheresis product - Avanish Mishra; Shih-Bo Huang; Taronish Dubash; Risa Burr; Jon F. Edd; Ben S. Wittner; Quinn E. Cunneely; Victor R. Putaturo; Akansha Deshpande; Ezgi Antmen; Kaustav A. Gopinathan; Keisuke Otani; et al. (Nature Communications)
Abstract Circulating Tumor Cells (CTCs) in blood encompass DNA, RNA, and protein biomarkers, but clinical utility is limited by their rarity. To enable tumor epitope-agnostic interrogation of large blood volumes, we developed a high-throughput microfluidic device, depleting hematopoietic cells through high-flow channels and force-amplifying magnetic lenses. Here, we apply this technology to analyze patient-derived leukapheresis products, interrogating a mean blood volume of 5.83 liters from seven patients with metastatic cancer. High CTC yields (mean 10,057 CTCs per patient; range 100 to 58,125) reveal considerable intra-patient heterogeneity. CTC size varies within patients, with 67% overlapping in diameter with WBCs. Paired single-cell DNA and RNA sequencing identifies subclonal patterns of aneuploidy and distinct signaling pathways within CTCs. In prostate cancers, a subpopulation of small aneuploid cells lacking epithelial markers is enriched for neuroendocrine signatures. Pooling of CNV-confirmed CTCs enables whole exome sequencing with high mutant allele fractions. High-throughput CTC enrichment thus enables cell-based liquid biopsy for comprehensive monitoring of cancer.